PENINGKATAN VIABILITAS BENIH DAN PERTUMBUHAN VEGETATIF AWAL JAGUNG PADA KONDISI SALIN DENGAN RHIZOBAKTERI INDIGENOUS PULAU TARAKAN - Eko Hary Pudjiwati; Siti Zahara (Plumula : Berkala Ilmiah Agroteknologi, 2020)
Saline stress greatly affects maize crops starting from germination, growth and productivity. The application of rhizobacteria can affect germination and plant growth in saline soils. This study aims to determine the effect of indigenous rhizobacteria on germination and early vegetative growth of maize. The research was carried out in two stages, the first was screening isolates that were able to provide good germination under saline conditions. The second stage was the test for 8 rhizobacterial isolates from the first stage of the initial vegetative growth of maize in saline conditions. The experimental design used in the first stage was a completely randomized design, with 23 rhizobacterial isolates and 2 controls as treatments, repeated 2 times. In the second stage, a randomized block design was used, 8 treatments of rhizobacteria isolates and 2 controls, with 5 replications. The results of the research in the first stage obtained 8 rhizobacterial isolates that were able to give a germination percentage of ≥ 70% and isolate B311 gave a germination percentage of 90%. In the initial vegetative growth test, isolate B19 was able to provide better initial vegetative growth in saline conditions than other isolates.